Diagnostic Yield of Emergency Department Arch-to-Vertex CT Angiography in Patients with Suspected Acute Stroke - Deipolyi, A.R. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Our aim was to investigate how often relevant diagnostic findings in an arch-to-vertex CTA scan, obtained specifically as part of the acute stroke CT protocol, are located in the head, neck, and upper chest regions. MATERIALS AND METHODS: Radiology reports were reviewed in 302 consecutive patients (170 men, 132 women; median ages, 66 and 73 years, respectively) who underwent emergency department investigation of suspected acute stroke between January and July 2010. Diagnostic CTA findings relevant to patient management were recorded for the head, neck, and chest regions individually. Additionally, the contributions to the total CTA scan effective dose were estimated from each of the 3 anatomic regions by using the ImPACT CT Dose Calculator. RESULTS: Of the 302 patients, 161 (54%) had relevant diagnostic findings in the head; 94 (31%), in the neck; and 4 (1%), in the chest. The estimated contributions to the total CTA scan dose from each body region, head, neck, and upper chest, were 14 ± 2%, 33 ± 5%, and 53 ± 6%, respectively. CONCLUSIONS: Most clinically relevant findings are in the head and neck, supporting inclusion of these regions in arch-to-vertex CTA performed specifically in patients with acute stroke in the emergency department. Further studies are required to investigate extending the scan to the upper chest because only 1% of patients in our study had clinically relevant findings in the mediastinum, yet half the CTA effective dose was due to scanning in this region.